The changing landscape of nontyphoidal salmonellosis: epidemiological patterns, imported cases and serovar distribution in Germany from 2012 to 2023 - Simon Brinkwirth; Achim Dörre; Klaus Stark; Anika Meinen (BMC Infectious Diseases)
Abstract Introduction Nontyphoidal Salmonella is a zoonotic foodborne pathogen that represents a global public health issue. In the European Union and Economic Area, about 66,000 cases of reported nonthyphoidal salmonellosis occurred in 2022, with about 9,100 cases in Germany. The aim of this study is to analyse the incidence and epidemiological characteristics as well as trends of salmonellosis in Germany from 2012 to 2023. Methods German national surveillance data on salmonellosis from 2012 to 2023 were analysed. Available information included demographics, notification dates, country of exposure, hospitalisation, and serovar. The incidence was calculated per 100,000 population, stratified by age, sex, and travel and hospitalisation history. A descriptive analysis was conducted. Results A total of 160,782 cases of salmonellosis were reported between 2012 and 2023 in Germany, with seasonal peaks occurring during the summer months. The incidence declined from 26 per 100,000 in 2012 to 13 per 100,000 in 2023. This decline was observed across all defined age groups, sex and regions. The proportion of imported cases increased since 2012, reaching a peak of 26% (n = 1,943) in 2023. The proportion of cases that resulted in hospitalisation remained relatively constant, accounting for approximately 30% of all cases. The incidence was higher in males and children under the age of five years. The most frequent serovars were S. Enteritidis and S. Typhimurium. From 2020 onwards, there was an increase in the number of unknown serovars. Conclusion The analysis of these surveillance data provided a good basis to monitor trends and to identify special population groups at risk. The decrease in the incidence of salmonellosis in Germany between 2012 and 2023 might reflect a positive trend in public health efforts and food safety. The increased proportion of imported cases highlights the higher importance of monitoring and addressing travel-related exposures. Ongoing efforts are essential to mitigate both domestic and imported salmonellosis cases, particularly in young children and older adults.